Two Cases of Heavy Chain MGUS - Jan Van Keer; Björn Meijers; Michel Delforge; Gregor Verhoef; Koen Poesen (Case Reports in Oncological Medicine)
Heavy chain diseases are rare variants of B-cell lymphomas that produce one of three classes of immunoglobulin heavy chains, without corresponding light chains. We describe two patients with asymptomatic heavy chain monoclonal gammopathy. The first patient is a 51-year-old woman with alpha paraprotein on serum immunofixation. The second case is a 46-year-old woman with gamma paraprotein on urine immunofixation. Neither patient had corresponding monoclonal light chains. Workup for multiple myeloma and lymphoma was negative in both patients. These two cases illustrate that heavy chain monoclonal gammopathy can exist in the absence of clinically apparent malignancy. Only a few reports of “heavy chain MGUS” have been described before. In the absence of specialized guidelines, we suggest a similar follow-up as for MGUS, while taking into account the higher probability of progression to lymphoma than to myeloma.